2018
DOI: 10.1021/acssuschemeng.7b04943
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of Biomineralized Calcium Carbonate: Correlation between the Thermal Behavior and Structural Characteristics of Avian Eggshell

Abstract: This study focused on the thermal decomposition of biomineralized CaCO 3 , using avian eggshell. Biomineralized CaCO 3 , which exhibits a specialized structure, is a possible source of CaO used across various applications, including CO 2 capture. An understanding of the relation between the thermal decomposition kinetics in producing CaO and the original structure of biomineralized CaCO 3 may contribute to the further effective use of biowastes. The thermal decomposition of avian eggshell occurs via two mass-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 112 publications
(138 reference statements)
3
25
0
Order By: Relevance
“…Cree et al [20] observed the first mass loss of the eggshell powder of 5% up to 700°C and the main mass loss (44%) occurred from 700°C to 900°C. Tsuboi et al [17] provided a very detailed description of the eggshell decomposition process, whereby the first mass loss begins with water vaporization, followed by the pore and crack formation, and then thermal degradation of the organic matter inside the outer shell membrane. Furthermore, the second mass loss of 43.23% corresponds to the thermal decomposition of the calcite in the eggshell.…”
Section: Thermal Decomposition Of the Solid Hatchery Wastementioning
confidence: 99%
See 1 more Smart Citation
“…Cree et al [20] observed the first mass loss of the eggshell powder of 5% up to 700°C and the main mass loss (44%) occurred from 700°C to 900°C. Tsuboi et al [17] provided a very detailed description of the eggshell decomposition process, whereby the first mass loss begins with water vaporization, followed by the pore and crack formation, and then thermal degradation of the organic matter inside the outer shell membrane. Furthermore, the second mass loss of 43.23% corresponds to the thermal decomposition of the calcite in the eggshell.…”
Section: Thermal Decomposition Of the Solid Hatchery Wastementioning
confidence: 99%
“…Normally, chicken eggshells can be converted into calcium oxide via a thermal decomposition process at temperatures higher than 780°C [17,18]. It should be noted that numerous researchers have conducted studies on the effects of various calcination conditions for synthesizing calcium oxide, e.g., the heating rate, the calcination temperature, and the calcination time [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that from temperature of 600 , the samples color was darker and eventually turns white at the highest calcination temperature of 900 . The thermal decompositon of eggshell carried out by means of two mass-loss processes: first, the primary thermal degradation of the outer shell membrane and second, the subsequent thermal decomposition of calcite in the shell matrix [21]. In addition to that, a higher calcination temperature produced odorless and more softest powder compare to uncalcined eggshell that give off stinky smell and more of hard and flakes powder.…”
Section: Visual Observationmentioning
confidence: 99%
“…Fortunately, the presence of water steam can promote the production of mesopores, even in favorable conditions for sintering. Many researchers suggested that, for the CaO-CaCO 3 looping system, water steam and adsorbent interact in two ways [54,55]. On the one hand, steam seems to affect the evolution of the pore structure, which is crucial to the cyclic working-capacity.…”
Section: Cao-based Adsorbentsmentioning
confidence: 99%